Comparative Study of the Effectiveness of Oral Fluconazole and Intravaginal Clotrimazole in the Treatment of Vaginal Candidiasis - Hiroshige Mikamo; Koji Izumi; Kunihiko Ito; Teruhiko Tamaya (Hindawi Limited, 1995)
Objective: A study was carried out to compare 3 treatment regimens for vaginal candidiasis.